👤

Bonjour pouvez vous m'aider
Exemples :
(2x + 6)(3x + 1) =
(x + 4)(5x - 2) =
(-x+3)(2x - 4) =
(4x + 1)(3x + 5) =
(2x + 3)(x – 4) =
(-5x + 1)(-2x - 3) =​


Bonjour Pouvez Vous MaiderExemples 2x 63x 1 X 45x 2 X32x 4 4x 13x 5 2x 3x 4 5x 12x 3 class=

Répondre :

bjr

avec * = multiplié par :

(2x + 6)(3x + 1) =

2x*3x + 2x*1 + 6*3x + 6*1 = 6x² + 2x + 18x + 6 = 6x² + 20x + 6

(x + 4)(5x - 2) =

x*5x + x*(-2) + 4*5x + 4*(-2) = 5x² - 2x + 20x - 8 = 5x² + 18x - 8

(-x+3)(2x - 4) =

-x*2x - x*(-4) + 3*2x + 3*(-4) = -2x² + 4x + 6x - 12 = -2x² + 10x - 12

à toi pour le reste..

Réponse :

(2x + 6)(3x + 1) =256

(x + 4)(5x - 2) =207

(-x+3)(2x - 4) =-12

(4x + 1)(3x + 5) =420

(2x + 3)(x- 4) =13

(-5x + 1)(-2x - 3) =312